2017
DOI: 10.1111/joss.12267
|View full text |Cite
|
Sign up to set email alerts
|

Comparing visual food images versus actual food when measuring emotional response of children

Abstract: With the continued growth of emotion research in the consumer sciences, it has become necessary to investigate approaches which are appropriate for use with children. The purpose of this study was to compare children's liking and emotional responses to food images and actual foods. In both studies, 8 foods were used as stimuli (fresh spinach, baby carrots, orange juice, white grapes, cheddar cheese, chocolate graham snacks, lychee gummy candy, and white bread). In the first study, children answered questions a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 17 publications
0
25
1
Order By: Relevance
“…This finding suggested that sweetness was not the only factor that influenced products’ preference. Food familiarization was reported as another component that could promote children's acceptance or preference of foods (Birch, ; Birch, Savage, & Ventura, ; Gallo, Swaney‐Stueve, & Chambers, ; Laureati, Cattaneo, Bergamaschi, Proserpio, & Pagliarini, ). For example, preschool children who were repeatedly exposed to tofu with either plain, salt, or sweet flavors, came to prefer the version that they were familiar with (Birch, ).…”
Section: Resultsmentioning
confidence: 99%
“…This finding suggested that sweetness was not the only factor that influenced products’ preference. Food familiarization was reported as another component that could promote children's acceptance or preference of foods (Birch, ; Birch, Savage, & Ventura, ; Gallo, Swaney‐Stueve, & Chambers, ; Laureati, Cattaneo, Bergamaschi, Proserpio, & Pagliarini, ). For example, preschool children who were repeatedly exposed to tofu with either plain, salt, or sweet flavors, came to prefer the version that they were familiar with (Birch, ).…”
Section: Resultsmentioning
confidence: 99%
“…The K‐State emoji scale discriminated across samples with traditionally popular flavors showing more positive responses than more polarizing flavors. Since all tasted samples were commercially available products, and potato chips tend to be a well‐liked food, it was expected that the scores would trend positive (Gallo et al, ; Gutjar et al, ; Schouteten, Vanwaeren, Lagast, et al, ; Schouteten, Verwaeren, Gellynck, et al, ). This was the case, however, participants still used all scale points to describe their emotional response as seen in Phase 1 (Swaney‐Stueve et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…With the dearth of available, acceptable methods for this type of research, less traditional mediums are being explored. One example of this is the use of emojis to record reactions to consumer products; there is a growing number of examples showcasing the capabilities of research with emojis in both adults and children (Gallo, Swaney‐Stueve, & Chambers, , ; Jaeger & Ares, ; Jaeger, Lee, et al, ; Jaeger, Vidal, Kam, & Ares, ; Schouteten, Verwaeren, Lagast, Gellynck, & De Steur, ; Schouteten, Verwaeren, Gellynck, & Almli, ; Swaney‐Stueve, Jepsen, & Deubler, ; Vidal, Ares, & Jaeger, ). As these new methods become available, it is critical they are tested for validity across age groups.…”
Section: Introductionmentioning
confidence: 99%
“…The CATA approach was successfully used with adults to investigate the dominant meaning of emoji [18,19]. With pre-adolescents it has been used previously in connection with emoji to evaluate emotional experiences of food products [8,9,12], but not yet to understand their meaning.…”
Section: Neutral Facementioning
confidence: 99%
“…However, emotion measurements (how they feel about food products) have been shown to provide additional information beyond liking measurements that can help to better understand food experiences [6,7]. Only a small body of research has assessed food-elicited emotions with children ranging from 7-13 years [8][9][10][11][12][13]. These studies recognized the advantage of using emoji to measure food-elicited emotions, which are intuitive, easy-to-use and child-friendly.…”
Section: Introductionmentioning
confidence: 99%